Informed trading, short sales constraints and futures' pricing - Pekka Hietala; Esa Jokivuolle; Yrjö Koskinen (Bank of Finland, 2000)
The purpose of this paper is to provide an explanation for relative pricing of futures contracts with respect to underlying stocks using a model incorporating short sales constraints and informational lags between the two markets.In this model stocks and futures are perfect substitutes, except for the fact that short sales are only allowed in futures markets.The futures price is more informative than the stock price, because the existence of short sales constraints in the stock market prohibits trading in some states of the world.If an informed trader with no initial endowment in stocks receives negative information about the common future value of stocks and futures, he is only able to sell futures.Uninformed traders also face a similar short sales constraint in the stock market.As a result of the short sales constraint, the stock price is less informative than the futures price even if the informed trader has received positive information.Stocks can be under- and overpriced in comparison with futures, provided that market makers in stocks and futures only observe the order flow in the other market with a lag.Our theory implies that: 1) the basis is positively associated with the contemporaneous futures returns; 2) the basis is negatively associated with the contemporaneous stock return; 3) futures returns lead stock returns; 4) stock returns also lead futures returns, but to a lesser extent; and 5) the trading volume in the stock market is positively associated with the contemporaneous stock return.The model is tested using daily data from the Finnish index futures markets.Finland provides a good environment for testing our theory, since short sales were not allowed during the period for which we have data (27 May 1988 - 31 May 1994).We find strong empirical support for the implications of our theory.
URN:NBN:fi:bof-20140807384
Keywords: 330